Feasibility of Augmented Reality Media for Ecosystem Learning in Primary Education: Expert Validation and User Trials - Cendani, Tinezia; Kristanto, Andi; Mariono, Andi (UNDIKMA, 2025)
This study aims to develop augmented reality application technology as a learning medium for ecosystem material in science subjects at the primary education level. The research belongs to a Research and Development (R&D) study employing the Holistic 4D Model (Define, Design, Develop, Deploy), limited to the Develop stage. The instrument used for data collection was an open-ended questionnaire to determine the feasibility of the media, with development subjects including expert review, one-on-one, and field test. Expert review involved media experts, subject matter experts, and instructional design experts who are competent in the field of educational technology. The one-on-one trial was conducted with three fifth-grade students in primary education, while the field test was carried out with 24 students at the same grade level. The results indicated that the Augmented Reality Media for Ecosystem Learning is highly valid. This was based on scores obtained from subject matter experts (3.80, highly valid category), media experts (3.83, highly valid category), and instructional design experts (3.81, highly valid category). The response to the media implementation reached 91% in the one-on-one trial and 87% in the field test. These findings demonstrate that the Augmented Reality Media for Ecosystem Learning is feasible to be used in learning within primary education.